Development of universal high-strength magnesium aluminosilicate glass-ceramic materials for armor protection - Savvova, Oksana Viktorivna; Tymofieiev, Vadym Dmytrovych; Voronov, Hennadii Kostiantynovych; Fesenko, Oleksii Igorovych (Національний технічний університет "Харківський політехнічний інститут", 2022)
The necessity of creating innovative protective structures for armoring machinery and equipment is analyzed. A comparative analysis of high-strength materials used for local and individual body armor has been carried out. The relevance of the development of domestic universal armored materials that combine high strength properties and radio transparency based on lightweight technological magnesium aluminosilicate glass-ceramic materials with high performance properties at the level of world analogues has been determined. Were formulated the purpose and tasks of the work, which consist in: analysis of the current state of development of glass-ceramic materials for armor protection; development of magnesium-aluminosilicate glass-ceramic materials with high armor resistance, impact resistance and radio transparency; investigation of the operational properties of the developed glass-ceramic materials and their armor resistance; assessment of the competitiveness of the developed glass-ceramic materials. A set of requirements for a glass matrix for obtaining protective glass-ceramic materials has been formulated. Compositions and technological parameters for the production of glass-ceramic materials under the conditions of two-stage low-temperature heat treatment have been developed. The study of the electrical properties of experimental glass-ceramic materials made it possible to establish the possibility of effective functioning of on-board wireless communication systems when using the developed materials as elements of armor protection. It was found that the developed glass-ceramic materials are characterized by high operational properties (KCU = 5.8 kJ/m²; HV = 10.4 GPa; K1C = 8.5 MPa∙m⅟ ²) and armor resistance STANAG 4569 (level 2). The competitiveness of the developed glass-ceramic materials based on mullite is analyzed. It has been established that a significant increase in fracture toughness and a decrease in the density of the developed material when comparing properties with a similar armor element (corundum based plate) will significantly reduce the weight of the armor elements by ≈1.4 times and its cost by five times, while maintaining its protective properties.

Проаналізовано необхідність створення інноваційних захисних структур для бронювання техніки і обладнання. Проведено порівняльний аналіз високоміцних матеріалів, які застосовуються для локального та індивідуального бронезахисту. Визначено актуальність розробки вітчизняних універсальних бронематеріалів що поєднують високі міцносні властивості та характеристики радіопрозорості на основі полегшених технологічних магнійалюмосилікатних склокристалічних матеріалів з високими експлуатаційними властивостями на рівні світових аналогів. Сфоромульовано мету та завдання роботи, які полягають у аналізі сучасного стану розробок склокерамічних матеріалів для бронезахисту; розробці магнійалюмосилікатних склокристалічних матеріалів з високою бронестійкістю, ударостійкістю та радіопрозорістю; дослідженні експлуатаційних властивостей розроблених склокристалічних матеріалів та їх бронестійкості; оцінці конкурентної здатності розроблених склокристалічних матеріалів. Сформульовано комплексу вимог до скломатриці для одержання захисних склокристалічних матеріалів. Розроблено склади та технологічні параметри одержання склокерамічних матеріалів в умовах двостадійної низькотемператуної термічної обробки. Дослідження електричних властивостей дослідних склокристалічних матеріалів дозволило встановити можливість ефективного функціонування бортових безпровідних систем зв’язку при застосуванні розроблених матеріалів як елементів бронезахисту. Встановлено, що розроблені склокристалічні матеріали характеризуються високими експлуатаційними властивостями (KCU = 5,8 кДж/м²; HV = 10,4 ГПа; K1C = 8,5 МПа·м⅟ ²) та бронестійкістю STANAG 4569 (2 рівень). Проаналізовано конкурентоздатність розроблених склокерамічних матеріалів на основі муліту та встановлено, що вагоме підвищення в’язкості руйнування та зниження щільності розробленого матеріалу при порівнянні з аналогічною пластиною на основі корунду дозволить суттєво знизити вагу бронеелементів у ≈ 1,4 рази та його вартість у 5 разів при збереженні його захисних властивостей. Визначено економічний ефект від впровадження вітчизняних склокерамічних матеріалів для бронезахисту.
Розробка універсальних високоміцних магнійалюміносілікатних склокерамічних матеріалів для бронезахисту
Keywords: armor plate; glass-ceramic material; mullite; competitive ability; бронеелемент; склокерамічний матеріал; муліт; конкурентна здатність